Social Representations of pregnancy among trans men - Danilo Martins Roque Pereira; Ednaldo Cavalcante de Araújo; Sheyla Costa de Oliveira; Anderson Reis de Sousa; Mariana Mercês Mesquita Espíndola; Milka Gabrielle de Lira Nóbrega West; Marclineide Nóbrega de Andrade Ramalho; Joecio Cordeiro Cardoso (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to understand the meanings and experiences of pregnancy among trans men in light of the Theory of Social Representations. Methods: this is a qualitative, descriptive and exploratory study, carried out with trans men selected for convenience and availability. Data production took place from September to October 2021, via the Google Meet® platform, based on interviews with a semi-structured script. Interview lexicographic textual analysis was performed using the Reinert method and instrumented by IRAMUTEQ version 7.0. Results: social representations of pregnancy involved a wide field of meanings, in which efforts were articulated to accept opportune and solitary pregnancy, fear of the parturition process and influence of physical and emotional changes. Final considerations: the study reinforces the importance of advanced nursing practice in assisting the pregnancy-puerperal cycle, based on the perspective of comprehensive care, equity in access to services and respect for differences.